Pengolahan Air Limbah Tahu Menggunakan Metode Elektrokoagulasi dan Adsorpsi Secara Kontinyu: Tofu Wastewater Treatment Using Continuous Electrocoagulation and Adsorption Method - Ninik Lintang Edi Wahyuni; Nurcahyo; Unung Leoanggraini; Robby Sudarman; Bambang Soeswanto; Emma Hermawati Muhari; Agustinus Ngatin; Rony Pasonang Sihombing (KOVALEN: Jurnal Riset Kimia, 2023)
Tofu wastewater contains a lot of protein therefore it is easily degraded to produce foul odors and harmful gases due to microbes. Protein levels can be reduced through the electrocoagulation method which is equipped with adsorption. The purpose of this study is to reduce the value of turbidity, TSS, and COD in tofu wastewater due to the influence of voltage in the electrocoagulation process which is equipped with an adsorption process. This research was conducted with an electrocoagulation process at a rate of 250L/min with voltage variations of 15, 20, and 24Volt in a 10L tank containing 3 pairs of aluminum (Al) electrodes connected with direct current. The output water from the electrocoagulation process flows into the settling basin and flows into the adsorption tank containing activated carbon adsorbent. Both of these continuous processes were the innovation of this research. Sampling was conducted every 10 minutes for analysis of turbidity, TSS, COD, and pH. The results of the output water analysis from the electrocoagulation process after passing through the precipitation and adsorption processes show that increasing the voltage results in the decrease of turbidity, TSS, and COD values, however, increased efficiency and pH. Thus, a voltage of 24V with a flow rate of 250mL/min resulted in the highest efficiency of the voltage variations (15, 20, and 24V) with a process time of 90 minutes with a turbidity impurity reduction efficiency value of 45.42% with a value of 41.36 NTU from 75.22NTU, TSS 91.42% with a decrease to 1827mg/L from 21288mg/L, and COD 55.56% with a COD value of 9600mg/L from 21600mg/L, and a process output water pH of 4.91, as well as a reduction in aluminum electrode weight of 1.024grams.